Housing tenure and disability in the UK: trends and projections 2004–2030 - Murphy, Michael; Grundy, Emily M. D. (Frontiers in Public Health, 2024)
Introduction Housing is a major influence on health. Housing tenure is associated with housing conditions, affordability, and security and is an important dimension of housing. In the UK there have been profound changes in both housing conditions and the distribution of households by tenure over the past century, that is during the lifetimes of the current population. Methods We firstly reviewed and summarise changes in housing conditions, housing policy and tenure distribution as they provide a context to possible explanations for health variations by housing tenure, including health related selection into different tenure types. We then use 2015-2021 data from a large nationally representative UK survey to analyse associations between housing tenure and self-reported disability among those aged 40-69 controlling for other socio-demographic factors also associated with health. We additionally examine changes in the association between housing tenure and self-reported disability in the population aged 25 and over in the first two decades of the 21st century and project trends forward to 2030. Results Results show that associations between housing tenure and disability by tenure were stronger than for any other indicator of socio-economic position considered with owner-occupiers having the best, and social renters the worst, health. Differences were particularly marked in reported mental health conditions and in economic activity, with 28% of social renters being economically inactive due to health problems, compared with 4% of owner-occupiers. Rates of disability have increased over time, and become increasingly polarised by tenure. By 2020 the age standardised disability rate among tenants of social housing was over twice as high as that for owner occupiers, with projections indicating further increases in both levels, and differentials in, disability by 2030. Discussion These results have substantial implications for housing providers, local authorities and for public health.